2021
DOI: 10.1177/14034948211019795
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the COVID-19 pandemic among migrants: An innovative, system-level, interdisciplinary approach is needed to improve public health

Abstract: The effects of the COVID-19 pandemic are amplified among socially vulnerable groups, including international migrants, in terms of both disease transmission and outcomes and the consequences of mitigation measures. Migrants are overrepresented in COVID-19 laboratory-confirmed cases, hospital admissions, intensive care treatment and death statistics in all countries with available data. A syndemic approach has been suggested to understand the excess burden in vulnerable populations. However, this has not stoppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Likewise, the higher hospitalization rates in EM would apparently not be in accordance with the phenomenon known as the "healthy immigrant effect" [35], although this gap in health levels between EM and natives has been questioned in Spain and other European countries [36]; moreover, controlling for comorbidity using propensity scores also raises the suspicion that it is not associated pathologies that increase the probability of hospitalization in EMs. Therefore, given that comorbidity, socioeconomic and demographic factors cannot be identified as responsible for the association between EM status and the risk of being hospitalized for COVID-19, one can only speculate, as has been recently suggested [37], whether language and cultural barriers, lack of knowledge about the functioning of the health system, sociopolitical conditioning factors or genetic and biological susceptibility might be behind these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the higher hospitalization rates in EM would apparently not be in accordance with the phenomenon known as the "healthy immigrant effect" [35], although this gap in health levels between EM and natives has been questioned in Spain and other European countries [36]; moreover, controlling for comorbidity using propensity scores also raises the suspicion that it is not associated pathologies that increase the probability of hospitalization in EMs. Therefore, given that comorbidity, socioeconomic and demographic factors cannot be identified as responsible for the association between EM status and the risk of being hospitalized for COVID-19, one can only speculate, as has been recently suggested [37], whether language and cultural barriers, lack of knowledge about the functioning of the health system, sociopolitical conditioning factors or genetic and biological susceptibility might be behind these differences.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Norway found that 35–50% of the confirmed cases of COVID-19 were in migrants, despite them only making up about 15% of the general population. [ 43 ]. Migrant workers are overrepresented in lower paid jobs and crowded living situations, and as such, are more vulnerable to the spread of COVID-19 [ 44 ].…”
Section: Risk Factors For Shs In Covid-19mentioning
confidence: 99%
“…Such factors consequently increase the risk of health problems. Among migrants, as with other groups, socioeconomic factors increased the risk and severity of COVID-19, exacerbating existing health inequalities during the pandemic [13-16]. However, in addition to socioeconomic factors, other aspects, unrecognised at the time, came into play, which resulted in increased health disparities among migrants during the pandemic [17].…”
Section: Background and Aimsmentioning
confidence: 99%